2021
DOI: 10.3389/fpls.2021.668847
|View full text |Cite
|
Sign up to set email alerts
|

Position Validation of the Dwarfing Gene Dw6 in Oat (Avena sativa L.) and Its Correlated Effects on Agronomic Traits

Abstract: An F6:8 recombinant inbred line (RIL) population derived from the cross between WAOAT2132 (Dw6) and Caracas along with the two parents were used to evaluate the genetic effects of Dw6 dwarfing gene on plant height and other agronomic traits in oat (Avena sativa L.) across three environments, and develop closely linked markers for marker-assisted selection (MAS) for Dw6. The two parents differed in all investigated agronomic traits except for the number of whorls. The RIL lines showed a bimodal distribution for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Both domesticated and wild barley are adapted to latitudinal clines, where reproductive phenology is controlled by genes responding to environmental cues 70 . Our identification of a GA20OX ortholog as a candidate gene for reproductive phenology corroborates previous work, where GA20OX loss of function was found to reduce PH and delay flowering 35 , 71 , 72 . Interestingly, GA20OX orthologs are semi-dwarfing genes implicated in the green revolution 73 .…”
Section: Resultssupporting
confidence: 90%
“…Both domesticated and wild barley are adapted to latitudinal clines, where reproductive phenology is controlled by genes responding to environmental cues 70 . Our identification of a GA20OX ortholog as a candidate gene for reproductive phenology corroborates previous work, where GA20OX loss of function was found to reduce PH and delay flowering 35 , 71 , 72 . Interestingly, GA20OX orthologs are semi-dwarfing genes implicated in the green revolution 73 .…”
Section: Resultssupporting
confidence: 90%
“…Height has often been associated with heading date, and this is reflected in the results here for QTLs on chromosomes 4A, 4D, 6D, and 7 A, but not 7D. While candidate genes for height were not examined, the height QTLs on chr6D are associated with the location of the dwarfing gene Dw 6 on Mrg04 of the consensus map 20 , 21 .…”
Section: Resultsmentioning
confidence: 76%
“…Milach and Federizzi (2001) and Yan et al. (2021) found that Dw6 , the most used dwarfing gene in commercial oat varieties (Milach & Federizzi, 2001), significantly reduces plant height and panicle length. In barley, the semi‐dwarf and slender dwarf suites of genes reduce plant height affecting culm and spike length (Kuczyńska et al.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, dwarf phenotypes in oat have usually been associated with shorter panicles (Brown et al, 1980;Marshall & Murphy, 1981;Meyers et al, 1985;Nirmalakumari et al, 2013). Milach and Federizzi (2001) and Yan et al (2021) found that Dw6, the most used dwarfing gene in commercial oat varieties (Milach & Federizzi, 2001), significantly reduces plant height and panicle length. In barley, the semi-dwarf and slender dwarf suites of genes reduce plant height affecting culm and spike length (Kuczyńska et al 2013).…”
Section: 3mentioning
confidence: 99%